Gratitude Profile Among High School Students During Covid-19 Pandemic - Theophanny Paula Theresia Rampisela; Cynthia Petra Haumahu; Criezta Korlefura; Yulian Hermanus Wenno; Vando Kristi Makaruku (International Journal of Education, Information Technology, and Others, 2021)
The aimed of this study is to determine gratitude index on secondary school students who study in Ambon during pandemic COVID-19. Gratitude in this article described as an emotion, moral factor and virtue in person (Emmons & McCullough, 2003). This research was administered among 185 students from eleven Secondary School in Ambon, used adaptation of 6 item The Gratitude Questionnaire-Six-Item Form (GQ-6). The result showed that students in secondary school scored low in Gratitude scale. Furthermore, the scale showed that the students have higher score on affective traits, meanwhile scored low on emphatic skills